The Phenomenon of Al-Naskh: A Brief Overview of The Key Issues - Ushama, Thameem (Jurnal Fiqh, 2006)
The phenomenon of al-naskh discussed over the ages still remains as one of the most outstanding issues in understanding the legal rulings of some of the verses of the Qur`an. This article presents a brief analysis of the meaning of the terms, examines the scopes, explores the benefits, and investigates the conditions for the occurrence of al-naskh followed by a brief highlight of its wisdoms. It also examines its genuine sources. It makes a critical study of the related issues regarding this phenomenon, especially the occurrence of al-naskh in the Qur`an and its kinds as enshrined in the writings of the classical exegetes and jurists. The highlight of the article is the critical exploration of the arguments of two schools of thought where a school stands by its occurrence and the other totally denies it.